Витоки категорії "правосуб'єктність" - Форманюк, Вікторія Василівна; Форманюк, Виктория Васильевна; Formanjuk, V. (My University, 2012)
The article is devoted to the formation of categories of personality in Roman law. The author proves his vision of the origins of the categories of personality. In this paper, based on a comprehensive study of the scientifi c literature by the author identifi es and analyzes the effi ciency category, capacity, legal status of persons.
Форманюк В. В. Витоки категорії "правосуб'єктність" / В. В. Форманюк // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України ; НУ ОЮА. – Одеса : Фенікс, 2012. – Вип.. 46. – С. 25-31.
Keywords: категорія "правосуб'єктність" у римському праві; дієздатність у римському праві; правовий статус особи за римським правом; правоздатність у римському праві; категория "правосубъектность" в римском праве; дееспособность в римском праве; правовой статус лица по римскому праву; правоспособность в римском праве; category of "personality" in Roman law; capacity in Roman law; the legal status of a person on Roman law; Standing in Roman law